Cultivar loss and conservation of genetic resources of the phureja potato (Solanum phureja L., Phureja Group) in Peru - Juan F. Seminario; Leónidas S. Concha-Tupayachi; Alejandro Seminario-Cunya; Tulio Medina-Hinostrosa; Wilsser Silva (Genetic Resources, 2025)
Solanum tuberosum L. Phureja Group, known in Peru as ‘phureja potato’ or ‘chaucha potato’ and as ‘criolla’ in Colombia, is characterized by its earliness and the absence of dormancy in the tubers. It stands out for its nutritional value and its contribution to food security. However, it faces a high risk of disappearance in Peru. This study assessed its current status by collecting historical data, ex situ and in situ conservation analyses, and genetic erosion studies in local communities. Historical information suggests that phureja was relevant and abundant in the past. Currently, ex situ collections include 69 accessions, of which the International Potato Center conserves a significant portion. As for in situ conservation, 116 accessions have been identified. However, since 1992, genetic erosion has been documented in six departments of Peru. The main causes include: lack of time for continuous cultivation, prioritization of dairy farming, low seed quality, preference for more commercial modern or traditional cultivars, and the expansion of mining projects. The critical situation of the phureja potato requires urgent measures to collect new information and evaluate the remaining genetic variability. This assessment is essential to develop conservation and sustainability strategies to ensure its survival and its contribution to Peru's food and cultural well-being.